Erratum - Jang, Kitae; Song, Myoung K.; Choi, Keechoo; Kim, Dong-Kyu (Transport, 2014)
"Erratum on the article ‘A bi-level framework for pricing of high-occupancy toll lanes’." Transport, 29(4), p. 466First Published Online: 16 Dec 2014